2008
DOI: 10.1093/eurheartj/ehn362
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in recurrent cardiovascular events with prasugrel compared with clopidogrel in patients with acute coronary syndromes from the TRITON-TIMI 38 trial

Abstract: AimsIn the TRITON-TIMI 38 trial, greater platelet inhibition with prasugrel reduced the first occurrence of the primary endpoint (cardiovascular death, MI, or stroke) compared with clopidogrel in patients with an acute coronary syndrome (ACS) undergoing planned percutaneous coronary intervention. We hypothesized that prasugrel would reduce not only first events but also recurrent primary endpoint events and therefore total events compared with clopidogrel.Methods and resultsPoisson regression analysis was perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
86
1
5

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 124 publications
(94 citation statements)
references
References 20 publications
2
86
1
5
Order By: Relevance
“…For example, competition for CYP 3A4 may explain why the antiplatelet effect of clopidogrel is reduced when given concomitantly with atorvastatin or dihydropyridine calcium channel blockers (CCBs). 46,47 Concomitant administration of dihydropyridine CCBs and clopidogrel also increased the risk of an adverse cardiovascular outcome (adjusted hazard ratio determined platelet activity that had safety and antiplatelet activity end points, and (2) [23][24][25][26][27][28] The studies were selected for this review with a focus on comparative data from randomized, controlled studies relating to the pharmacological and/or clinical properties of prasugrel, and data/commentary from the FDA review document were also included. 12 However, in order to place the prasugrel data into context within current clinical practice, comparative information on the pharmacologic and clinical profile of clopidogrel from smaller studies was also identified via PubMed.…”
Section: Drug-drug Interactionsmentioning
confidence: 99%
See 4 more Smart Citations
“…For example, competition for CYP 3A4 may explain why the antiplatelet effect of clopidogrel is reduced when given concomitantly with atorvastatin or dihydropyridine calcium channel blockers (CCBs). 46,47 Concomitant administration of dihydropyridine CCBs and clopidogrel also increased the risk of an adverse cardiovascular outcome (adjusted hazard ratio determined platelet activity that had safety and antiplatelet activity end points, and (2) [23][24][25][26][27][28] The studies were selected for this review with a focus on comparative data from randomized, controlled studies relating to the pharmacological and/or clinical properties of prasugrel, and data/commentary from the FDA review document were also included. 12 However, in order to place the prasugrel data into context within current clinical practice, comparative information on the pharmacologic and clinical profile of clopidogrel from smaller studies was also identified via PubMed.…”
Section: Drug-drug Interactionsmentioning
confidence: 99%
“…[24][25][26][27][28] Three examined patient subgroupsstent recipients, 27 patients with STEMI, 28 and patients with diabetes 26 -and 2 examined end points-recurrent events 25 and early/late events. 24 In all 3 TRITON patient subgroup analyses, prasugrel was randomized, double-blind trial involving 13,608 patients with moderate-to high-risk ACS with scheduled PCI.…”
Section: Food Effectmentioning
confidence: 99%
See 3 more Smart Citations